2015
DOI: 10.1016/j.athoracsur.2015.04.063
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Sealing Using the HARMONIC ACE+ Shears for Video-Assisted Thoracoscopic Surgery Lobectomy

Abstract: PA branches sealed using the HARMONIC ACE+ in a simulated ex vivo model were able to sustain high intraluminal pressures. ACE-sealed vessels burst at mean bursting pressures equal to or greater than the VES-stapled vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…Ex vivo studies evaluated burst pressures of PA branches sealed with different energy vessel-sealing devices and with standard endostaplers. 6,15 Results showed that PAs sealed with ultrasonic energy can sustain higher pressures than PAs sealed with advanced bipolar energy devices or endostaplers. In an animal survival study, 10 lobectomies using the device were completed in 10 dogs without any bleeding complications at 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo studies evaluated burst pressures of PA branches sealed with different energy vessel-sealing devices and with standard endostaplers. 6,15 Results showed that PAs sealed with ultrasonic energy can sustain higher pressures than PAs sealed with advanced bipolar energy devices or endostaplers. In an animal survival study, 10 lobectomies using the device were completed in 10 dogs without any bleeding complications at 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety PA branches with a mean diameter of 5.2 mm (range, 1.7-11.4 mm) had a mean burst pressure of 333 mm Hg (range, 84-1415 mm Hg) with no seal failure. 17 Other studies with smaller sample size have shown similar results with bursting pressures far beyond physiological PA pressures. 11,16 The ACE is approved for vessel sealing up to 7 mm diameter.…”
Section: Discussionmentioning
confidence: 57%
“…The safety and effectiveness of ultrasonic energy vesselsealing devices for PA branch sealing has been reported in several ex vivo human lung specimen studies and animal studies. 11,[16][17][18] Burst pressure was measured on human PA stumps sealed with the ACE on lung specimens in a study published by our group. Ninety PA branches with a mean diameter of 5.2 mm (range, 1.7-11.4 mm) had a mean burst pressure of 333 mm Hg (range, 84-1415 mm Hg) with no seal failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that part of the media remained at the sealed zone, which was stained with a-SMA and EVG stain. Electron microscopic findings of PA branches sealed with Harmonic Ace+ Shears in a human ex vivo model demonstrated various microscopic sealing patterns [7]. One-third of the sealed PAs presented invagination of the media and absence of melting.…”
Section: Discussionmentioning
confidence: 96%
“…Open and endosurgical stapling devices have become the standard instruments for closing the large pulmonary vessels [6], whereas the small pulmonary vessels are manually ligated with a suture or divided using a vessel-sealing device (VSD). Advanced bipolar and ultrasound technologies are still being evaluated in various trials [7][8][9]. Safe division of the pulmonary vessels, especially the pulmonary artery (PA), during anatomical lung resection, is critically important.…”
Section: Introductionmentioning
confidence: 99%